Evaluation of the financial condition of the companies of transport and storage section in times of economic crisis - taxonomic analysis = Ocena kondycji finansowej przedsiębiorstw sekcji transport i gospodarka magazynowa w czasie kryzysu gospodarczego - analiza taksonomiczna - Jędrzejczak-Gas, Janina; Kużdorowicz, Paweł (Zielona Góra: Faculty of Economics and Management Press)
The aim of the article is an evaluation of the financial condition of the companies of transport and storage section (section H) based on synthetic indicator in times of economic crisis. The first part of the paper discusses theoretical issues relating to the construction of synthetic measures. In the second part of the paper, a comparative study of the financial condition of the companies of transport and storage section in comparison with the financial condition of the companies in other sections was presented. This study was carried out on the basis of a synthetic financial condition indicator constructed with use of the model method.
Keywords: przedsiębiorstwo; transport i gospodarka magazynowa; kondycja finansowa; kryzys gospodarczy; miara syntetyczna; enterprises; transport and storage section; financial condition; economic crisis; synthetic measure